Pengaruh Asal Populasi, Komposisi Media dan Dosis Pupuk NPK terhadap Kemampuan Berkualitas tanaman pangkas Pulai darat (Alstonia angustiloba Miq.) - Mashudi Mashudi (Jurnal Pemuliaan Tanaman Hutan, 2010)
The aim of this experiment was to investigate effect of population sources, media composition and NPK fertilizer dosage toward sprouting ability of Alstonia angustiloba Miq. Cutting. This experiment was arranged in completely randomized design with factorial setting. The research used 3 factors, I,e.population sources (banten, Pendopo, Lubuk Linggau and Solok); media compositions (top soil, top soil : Compost : husk charcoal 3 : 2 : 1, top soil : compost : husk charcoal 4 : 2 : 1, Top soil : compost :husk charcoal 5 : 2 : 1 and top soil : compost : husk charcoal 6 : 2 : 1) and NPK fertilizer dosage (0g,5 g. 10 g, 15 g and 20 g). The results showed that media composition variantions did not give significant effect on parameters measured. The best of length and diameter of sprouts, number of nodus and number of leaves were significantly produced by 20 g NPK fertilizer dosage. Pendopo popupation significantly produced the best length sprouts, while Banten population produced the best number of nodus and Lubuk Linggau population produced the best diameter sprouts and the highest number of sprouts. Interaction of NPK fertilizer dosage and population sources gave significant influence on number of sprouts, whit the best interaction was 10 g dosage of NPK fertilizer vs Lubuk Linggau population (1.79).